Aplicación de un programa de experiencias científicas para desarrollar la capacidad investigativa en niños de cinco años de edad en una I.E.P. de Breña - Hinostroza Zuta, Jesica (2014)
Research of pre experimental type. The present research aimed to identify significant differences between pre and post test moments after an application of a program of scientific experiences in a sample of 20 children of 5 years old from preschool level of the Breña distric (capital of Lima). For this purpose, an instrument was developed to measure the observation and problem solving components. For treatment were developed 20 sessions of scientific experiences with focus on discovery learning. The findings corroborated that there was a significant improvement in research ability and in its three components; with significance less than 0.05. From descriptive results, a higher benefit was demonstrated in problem solving dimension reflected in its measuring ranges.